Non-Surgical Resolution of Inflow Cannula Obstruction of a Left Ventricular Assist Device: A Case Report - Lee, Yoonseo; Sung, Kiick; Kim, Wook Sung; Jeong, Dong Seop; Shinn, Sung Ho; Cho, Yang Hyun (Journal of chest surgery, 2021)
A 55-year-old woman who had received an implantable left ventricular assist device 3 months earlier presented with dyspnea and a low-flow alarm of the device. Computed tomography and log-file analysis of the device system suggested inflow cannula obstruction. Since the patient had cardiogenic shock due to pump failure, venoarterial extracorporeal membrane oxygenation (ECMO) was initiated. With ECMO, surgical exchange of the pump was considered. However, the obstruction spontaneously resolved without surgical intervention. It turned out that an obstructive thrombus was washed out by rebooting the pump. Moreover, the thrombus was embolized in the patient's left subclavian artery. The patient underwent heart transplantation 4 months after the pump obstruction accident and continued to do well.